IBEROAMERICA AND TRANSATLANTIC PARTNERSHIP: CHALLENGES AND PROSPECTS - V. . Tayar (Ибероамериканские тетради, 2016)
The subject of research is connected with the possibility that in the near future on the economic world map there can appear a new trading bloc - Transatlantic Trade and Investment Partnership (TTIP) between the EU and the USA. In article are analyzed challenges and prospects from this contract for Ibero-American countries (Spain, Portugal and Latin American y Caribbean countries).